Theory, Musicology and Antón Pirulero. (A Several-Part Rondo) (Revista Argentina de Musicología, 2018)
In light of the numerous reports on the death of theory and the alleged arrival of a post-theoretical era, I review some of the key moments in the history of the debate around the so-called theoretical turn in the humanities, including its reception by musicology. I examine the body of scholarly literature that thematizes the idea of an “after theory”–whether to celebrate or resist it–and identify five recurring warnings proceeding from both the critical voices raised against theory and theory’s own self-criticism.Against this background, I propose a reflection on our engagement with theory in the everyday practice of the discipline. I use the nursery rhyme Antón Pirulero as a ritornello to frame the different “episodes” through which the text perambulates. Even though it might seem so, this choice is neither casual nor flippant. The history of the Antón Pirulero in Hispanic-American culture from the 17th century onwards, which I explore towards the end, provides the key to the criticism put forward in the article.
Keywords: musicology; theory; epistemology; “death of theory”; “after theory”